Role of Customer Engagement in Customer Loyalty for Retail Service Brands: Customer Orientation of Salesperson as a Mediator - Srivastava, Mallika (Indian Journal of Marketing, 2019)
This paper examined the role of customer engagement in customer loyalty for retail service brands. It further explored the role of Customer Orientation of Salesperson as a mediating variable between Customer Engagement and Customer Loyalty. A cross-sectional research on retail customers through questionnaire was conducted. The population of the study included retail urban customers of Pune and Bangalore cities in India. Responses were analyzed using factor analysis and PROCESS procedure for SPSS. The proposed model attempted to evidence the partial mediation effect of Customer Orientation of Salesperson between Engagement and Loyalty. The study established and confirmed the relationship between Engagement and Loyalty as in the literature. The effects of Engagement on Loyalty have been known, yet the function of Customer Orientation dimensions as mediators between Engagement and Loyalty intention is the original contribution of the study. This study was undertaken among an explicit group of retail customers. Thus, it confined generalization of outcomes to other population. This study elucidated the significance of customer engagement for accomplishing customer loyalty for the Indian retail sector. This awareness would enable retail outlets to equip themselves against the developing online markets. The brick and mortar shops, if they give more attention to the training of salespersons towards customer orientation and keep their customers engaged so that they are more positive towards the salesperson, would enhance the customer loyalty for their customers. Thus, the managerial efforts would contribute towards efficient improvement of the traditional retail industry against the online market.